2023
DOI: 10.1002/iid3.984
|View full text |Cite
|
Sign up to set email alerts
|

Arbidol: The current demand, strategies, and antiviral mechanisms

Yue Kang,
Yin Shi,
Silu Xu

Abstract: BackgroundHigh morbidity and mortality of influenza virus infection have made it become one of the most lethal diseases threatening public health; the lack of drugs with strong antiviral activity against virus strains exacerbates the problem.MethodsTwo independent researchers searched relevant studies using Embase, PubMed, Web of Science, Google Scholar, and MEDLINE databases from its inception to December 2022.ResultsBased on the different antiviral mechanisms, current antiviral strategies can be mainly class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 117 publications
(286 reference statements)
0
2
0
Order By: Relevance
“…[94][95][96] It is a hydrophobic molecule capable of forming aromatic stacking interactions with certain amino acid residues, which contributes to its ability to directly act against viruses. Its antiviral activity may also be due to its interactions with the aromatic residues within the viral glycoproteins involved in fusion and cellular recognition, 97,98 the plasma membrane to interfere with clathrin-mediated exocytosis and intracellular trafficking, 99 or directly with the viral lipid envelope itself. As indicated by its SAR graph, the binding pocket of the HA protomers with arbidol is a hydrophobic cavity at the interface of the HA protomers in the upper region of the stem.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…[94][95][96] It is a hydrophobic molecule capable of forming aromatic stacking interactions with certain amino acid residues, which contributes to its ability to directly act against viruses. Its antiviral activity may also be due to its interactions with the aromatic residues within the viral glycoproteins involved in fusion and cellular recognition, 97,98 the plasma membrane to interfere with clathrin-mediated exocytosis and intracellular trafficking, 99 or directly with the viral lipid envelope itself. As indicated by its SAR graph, the binding pocket of the HA protomers with arbidol is a hydrophobic cavity at the interface of the HA protomers in the upper region of the stem.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…Some compounds exert antiviral effects by acting on host receptors. Arbidol (ARB), as a broad-spectrum antiviral, can interfere with virus entry or the membrane fusion of SARS-CoV-2 ( Kang et al., 2023 ). On the one hand, ARB inhibits the interaction between the S protein and ACE2.…”
Section: Treatments Targeting Host Factorsmentioning
confidence: 99%
“…54,55 Arbidol is an anti-influenza medication and has been shown to have antiviral effects on other viruses as well as immunomodulatory effects. 56 ■ STRUCTURAL PROTEINS OF ALPHAVIRUSES AS TARGETS A few studies have reported small molecule inhibitors of CP, E2, and 6K proteins. The multifunctional capsid protein is essential in genome encapsulation, virus budding, and virion assembly.…”
Section: Strategymentioning
confidence: 99%
“…This effort also led to the identification of resistant clones that bear G117R or D119 K mutation close to the binding pocket of nsP3MD. While there is no direct evidence yet that the compounds interfere with the biochemical roles of the nsP3MD, the significant loss of Additionally, a couple of in silico studies have predicted that naringenin (56), a lanthionine synthetase C-like 2 ligand, NSC61610 (57), and macrodomain 1 inhibitor (NSC670283, 58) have high affinity for CHIKV's nsP3MD. 118,119 Nonstructural Protein 4.…”
Section: ■ Nonstructural Proteins As Targetsmentioning
confidence: 99%
See 1 more Smart Citation